SLEEP AS A FOUNDATION OF SOCIAL HEALTH: A STUDY OF ADOLESCENT HEALTH AND SLEEP QUALITY - Ksenia Yu. Ledyankina (Russian Studies in Culture and Society)
Objective. This study aims to analyze the quality of sleep among adolescents aged 15-18 years and to identify factors contributing to sleep deprivation. The main goal of the work is to assess the impact of sleep patterns on the health and emotional well-being of adolescents, as well as to develop recommendations for improving sleep quality.